Regulação emocional e solidão em idosos: interfaces com identidade sexual e de gênero - Gabas, Arthur Fornazari (Universidade Federal de São Carlos, 2025)
Significant interpersonal relationships are a protective factor against loneliness. Relationships are constructed during a person’s lifetime, using skills such as emotional regulation. However, it is possible that the development of repertoires to deal with emotional issues is influenced by social factors, such as beliefs, norms and social practices related to people's identities. Two key dimensions of identity are those based on sexuality and gender. There is little information in the research literature regarding the effects of identity on the use of emotional regulation strategies, or on links between these repertoires and perceptions of loneliness in old age. The objectives of this research, therefore, were: (a) to compare the use of emotional regulation strategies and perceptions of loneliness in people over 50 years of age, considering the influence of sexuality and gender; and (b) to evaluate whether there is a significant relationship between the use of emotional regulation skills and feelings of loneliness. Study participants were 102 cisgender individuals, with a mean age of 62 years (SD = 7.2), ranging from 50 to 89 years. There were 71 women and 31 men; 82 participants were heterosexual and 20 were homosexual. Education levels ranged from an incomplete elementary school education to postgraduate studies. Data collection occurred mostly online, using Google Forms. The Emotional Self-Regulation Scale - Adult Version, the UCLA Brazilian Loneliness Scale and a Sociodemographic Questionnaire were used. When comparing groups using the Mann-Whitney U test, there were no statistically significant differences with respect to sexuality. Considering gender, women reported experiencing emotional freezing reactions more frequently than the men. Finally, a moderate correlation was found between the use of adaptive emotion regulation strategies (total score) and perceptions of loneliness (rs = -0.48, p < 0.001). Possibly, the high level of education of the participants, an uncommon qualification among people over 50 years old, may indicate that they had high skills to overcome social barriers. Considering the strength of the relationship between emotional regulation skills and perceptions of loneliness, in future studies it will be important to develop and evaluate interventions to help older people who feel lonely, by promoting the development of their adaptive emotion regulation skills.
Emotional regulation and loneliness among the elderly: interfaces with sexual and gender identities
Keywords: Velhice LGBT; Solidão; Regulação emocional; Manutenção de relacionamentos; Elderly LGBT; Loneliness; Emotion regulation; Relationship maintenance; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::RELACOES INTERPESSOAIS